External imbalance of the countries in the Eurozone - Janicka, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The financial crisis that hit the Eurozone made it necessary to reconsider the mechanisms of its functioning, as the source of the zone crisis is beyond doubt the systemic one. In the Euro Area did not work (and still does not work) symmetric mechanism leading to compensate the current account balances in both surplus and deficit countries. In consequence the growing external imbalances of the member countries and blocking by the integration processes the compensatory mechanisms which allow to restore the balance became the main reasons of the Eurozone crisis. The aim of the paper is to analyze the state of the external balance of euro area member states on the basis of two selected indicators – current account balance and net international investment position, both referred to GDP, in the context of EU action taken towards the problem of macroeconomic imbalances.